Some Generalized Difference Sequence Spaces Defined by Ideal Convergence and Musielak-Orlicz Function - Awad A. Bakery; Elsayed Abdelbayen Elnour Mohamed; Mohamed Alamin Ahmed (Abstract and Applied Analysis)
In the present paper we introduced the ideal convergence of generalized difference sequence spaces combining de La Vallée-Poussin mean and Musielak-Orlicz function over n-normed spaces. We also study some topological properties and inclusion relation between these spaces.